Laboratory methods of test for determination of smoke generation characteristics of cellular plastics and cellular rubber materials. Method for testing a 25 mm cube test specimen of low density material (up to 130 kg/m3 ) to continuous flaming conditions Part 1, (9th August 1974) - British Standards Institution,
No abstract available